The Influence of Community Language Learning Method on Descriptive Text Reading Skills in Junior High School Students - Wahyu Satya Gumelar; Khodijatul Kubro (Didaktika: Jurnal Kependidikan, 2024)
This study aims to determine the effect of the Community Language Learning method on the descriptive text reading skills of eighth-grade junior high school students. The research population consists of eighth-grade students, with a sample of 50 students, where 25 students were selected as the experimental group and the remaining 25 as the control group. The study employs an experimental research design because it is quantitative in nature and uses the T-Test method. The research data was collected through evaluation tests. The analysis results show that the observed t-value is greater than the t-table value (3 > 2.00) at a 0.05 significance level with 48 degrees of freedom, indicating that there is a significant effect of the Community Language Learning method on the descriptive text reading skills of eighth-grade students at SMP Islam Al-Ifadah.